Oxygen resuscitation and oxidative-stress biomarkers in premature infants - Kumar VH; Carrion V; Wynn KA; Nielsen L; Reynolds AM; Ryan RM (Dove Medical Press, 2014)
Vasanth HS Kumar,1 Vivien Carrion,1 Karen A Wynn,1 Lori Nielsen,1 Anne Marie Reynolds,1 Rita M Ryan2 1Department of Pediatrics, The Women and Children's Hospital of Buffalo, Buffalo, NY, 2Department of Pediatrics, Medical University of South Carolina, Charleston, SC, USA Background: Resuscitation of premature infants with 100% O2 may initiate significant oxidant stress during development, predisposing them to bronchopulmonary dysplasia. In the study reported here, we examined the effects of three different oxygen concentrations at resuscitation on oxygen saturations (SpO2) and oxidant stress in premature infants. Study design: Infants <32 weeks gestational age were randomized to 21%, 40%, or 100% O2 and resuscitated as per 2005 neonatal resuscitation guidelines. Oxygen groups and SpO2 were unmasked at 10 minutes of age and FiO2 adjusted to maintain an SpO2 of 85%–95% for the next 20 minutes. Blood was collected at 24 hours, 1 week, and 4 weeks for measurement of the oxidative-stress markers, such as a reduced glutathione (GSH) to oxidized glutathione (GSSG) ratio (GSH/GSSG), nitrotyrosine levels, and 8-hydroxydeoxyguanosine (8-OHdG) levels. The study was stopped at 30% enrollment following publication of the 2010 neonatal resuscitation guidelines. Results: We enrolled 18 patients during the study period. SpO2 increased over time (P<0.0001); however, this increase was not different among the three oxygen groups in the first 10 minutes after birth. FiO2 was significantly higher in the 100% O2 group, despite weaning (P<0.02) to maintain target saturations at 30 minutes of age. The GSH/GSSG ratio was significantly lower in the 100% O2 group at 24 hours than in the other groups (P<0.01). Plasma nitrotyrosine was significantly higher in the 40% and 100% O2 groups over time (P<0.01). Levels of 8-OHdG were significantly higher at 4 weeks compared with at 24 hours, independent of the oxygen group (P<0.0001). Conclusion: In this study, we defined the natural evolution of SpO2 in the first 10 minutes of life with exposure to three different concentrations of oxygen. Randomization to higher FiO2 led to higher total oxygen exposure at resuscitation, and this was significantly correlated with markers of systemic oxidant stress. Keywords: oxygen saturation, systemic oxidant stress, GSH/GSSG ratio, nitrotyrosine, resuscitation